2014
DOI: 10.1038/bcj.2014.69
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of minimal residual disease detection by multiparameter flow cytometry and enhanced ASO RQ-PCR in multiple myeloma

Abstract: Multiparameter flow cytometry (MFC) and allele-specific oligonucleotide real-time quantitative PCR (ASO RQ-PCR) are the two most sensitive methods to detect minimal residual disease (MRD) in multiple myeloma (MM). We compared these methods in 129 paired post-therapy samples from 22 unselected, consecutive MM patients in complete/near complete remission. Appropriate immunophenotypic and ASO RQ-PCR-MRD targets could be detected and MRD analyses constructed for all patients. The high PCR coverage could be achieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 27 publications
(31 reference statements)
1
32
0
1
Order By: Relevance
“…86 Subsequent comparisons between PCR-and MFC-based MRD monitoring showed that, except for a few discordant cases, both techniques provided highly concordant results (Figure 3). 60,64,87,88 The initial positive experience by the Spanish and United Kingdom groups led to the implementation of their corresponding 4-and 6-color MFC approaches in large clinical trials. In the Programa para el Estudio de la Terapéutica en Hemopatías Malignas/ Grupo Español de MM (PETHEMA/GEM) 2000 study, flow MRD was identified as the most relevant prognostic factor in a series of 295 newly diagnosed MM patients receiving uniform treatment including HDT/SCT.…”
Section: Transplant-eligible Patientsmentioning
confidence: 99%
“…86 Subsequent comparisons between PCR-and MFC-based MRD monitoring showed that, except for a few discordant cases, both techniques provided highly concordant results (Figure 3). 60,64,87,88 The initial positive experience by the Spanish and United Kingdom groups led to the implementation of their corresponding 4-and 6-color MFC approaches in large clinical trials. In the Programa para el Estudio de la Terapéutica en Hemopatías Malignas/ Grupo Español de MM (PETHEMA/GEM) 2000 study, flow MRD was identified as the most relevant prognostic factor in a series of 295 newly diagnosed MM patients receiving uniform treatment including HDT/SCT.…”
Section: Transplant-eligible Patientsmentioning
confidence: 99%
“…Firstly, clonality, i.e., the clonal Ig gene rearrangement(s) presenting in tumour PCs, from diagnostic BM samples is detected by qualitative PCR using consensus primers for genomic DNA (or cDNA in some studies (Ladetto et al , ; Rasmussen et al , ; Verhagen et al , ; Gerard et al , ; Sarasquete et al , ). In this regard, consensus primers developed by the BIOMED‐2 group in the form of several multiplex primer sets are the most widely used (van Dongen et al , ; Sarasquete et al , ; Martinez‐Lopez et al , ; Puig et al , ; Silvennoinen et al , ). Multiple immunoglobulin gene rearrangements are used as MRD targets in MM, including IGH complete VDJ and IGH incomplete DJ rearrangements, IGK deletion (Kde), IGK VJ and IGL VJ rearrangements (Gonzalez et al , ; Puig et al , ; Silvennoinen et al , ; Bai et al , ).…”
Section: Allele‐specific Oligonucleotide Pcrmentioning
confidence: 99%
“…In this regard, consensus primers developed by the BIOMED‐2 group in the form of several multiplex primer sets are the most widely used (van Dongen et al , ; Sarasquete et al , ; Martinez‐Lopez et al , ; Puig et al , ; Silvennoinen et al , ). Multiple immunoglobulin gene rearrangements are used as MRD targets in MM, including IGH complete VDJ and IGH incomplete DJ rearrangements, IGK deletion (Kde), IGK VJ and IGL VJ rearrangements (Gonzalez et al , ; Puig et al , ; Silvennoinen et al , ; Bai et al , ). Clonal PCR bands are sequenced by Sanger sequencing, and sequencing data is analysed with the ImMunoGeneTics (IMGT) V‐QUEST system (http://www.imgt.org) or the National Center for Biotechnology Information Basic Local Alignment Search Tool (NCBI BLAST; https://blast.ncbi.nlm.nih.gov/) to identify the patient‐specific sequence of the corresponding tumour PC CDR3 region.…”
Section: Allele‐specific Oligonucleotide Pcrmentioning
confidence: 99%
“…Thus, 20 clinical trials of newly diagnosed myeloma patients with information on MRD and clinical outcomes were identified and assessed for inclusion in this metaanalysis. Upon careful review of the 20 identified studies (12-14, 16, 18, 21, 58-71), four studies were excluded because they reported on ASCT (61-63, 71); seven were excluded because they did not evaluate the association between MRD status and PFS and/or OS (16,21,(64)(65)(66)(67)(68); four were excluded because they analyzed overlapping cohorts of patients (duplicates) (13,14,18,69); and one was excluded because the timing of MRD analysis was not specified (70). Four studies with information on MRD status and HR for PFS were included in the final analysis (12,(58)(59)(60).…”
Section: Mskcc/nci Meta-analysismentioning
confidence: 99%